2020
DOI: 10.1038/s41598-020-78577-8
|View full text |Cite
|
Sign up to set email alerts
|

Photon versus carbon ion irradiation: immunomodulatory effects exerted on murine tumor cell lines

Abstract: While for photon radiation hypofractionation has been reported to induce enhanced immunomodulatory effects, little is known about the immunomodulatory potential of carbon ion radiotherapy (CIRT). We thus compared the radio-immunogenic effects of photon and carbon ion irradiation on two murine cancer cell lines of different tumor entities. We first calculated the biological equivalent doses of carbon ions corresponding to photon doses of 1, 3, 5, and 10 Gy of the murine breast cancer cell line EO771 and the OVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 56 publications
0
16
1
Order By: Relevance
“…The characteristics of included ( 13 15 , 18 34 ) studies are summarized in Table 1 . Briefly, 13 carbon ion irradiation and seven proton irradiation studies were included in our final SR; these studies were published between 2004 and 2021.They were conducted in 7 different countries: Japan, Germany, Belgium, Italy, Korea, the United States of America, and Lithuania.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of included ( 13 15 , 18 34 ) studies are summarized in Table 1 . Briefly, 13 carbon ion irradiation and seven proton irradiation studies were included in our final SR; these studies were published between 2004 and 2021.They were conducted in 7 different countries: Japan, Germany, Belgium, Italy, Korea, the United States of America, and Lithuania.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, 13 carbon ion irradiation and seven proton irradiation studies were included in our final SR; these studies were published between 2004 and 2021.They were conducted in 7 different countries: Japan, Germany, Belgium, Italy, Korea, the United States of America, and Lithuania. Of these studies, almost all used human pancreatic cancer cell lines, such as AsPC-1, BxPc-3, MIA PaCa-2, PANC-1, and PK45, only one ( 18 ) used transgenic mice cell lines (PDA30364/OVA). The studies varied in the initial energy, averaged LET, SOBP, radiation doses, and dose rates used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also at the moment it is not clear whether or not high LET radiation will enhance the infiltration capability of T cells in the tumor microenvironment, or whether the latter will be modified in other aspects. First experimental results ( 78 80 ) do not show a clear picture yet, while the tissue sparing effect of particle irradiation indeed seems to be beneficial regarding lymphocyte deprivation ( 81 ). Thus the multiple perspectives and open questions associated with the use of high LET RIT warrant further preclinical experiments, which are able to answer the speculative and encouraging expectations presented above.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Hartman et al ( 53 ) found in vitro that CIRT and photon beam radiotherapy had common radiobiological properties such as induction of cell cycle arrest, surface expression of immune-modulating molecules, and activation of cytotoxic lymphocytes. Nevertheless, other authors have suggested that CIRT-induced immune activation might be more potent.…”
Section: Immunological Rationale Of Cirt For Accmentioning
confidence: 99%